1999
DOI: 10.1016/s0002-9270(99)00133-1
|View full text |Cite
|
Sign up to set email alerts
|

Additional investigations fail to alter the diagnosis of irritable bowel syndrome in subjects fulfilling the Rome criteria

Abstract: Examination of screening tests in 1452 patients with an established history of IBS revealed an incidence of lactose malabsorption comparable to that in the general U.S. population and a low incidence of thyroid dysfunction, ova and parasite infestation, or colonic pathology. The limited detection rates, added costs, and inconvenience of these tests suggest that their routine use in the diagnostic evaluation of established IBS patients should be scrutinized.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(56 citation statements)
references
References 0 publications
0
54
0
2
Order By: Relevance
“…Similar study observed 30% of the population suffering from thyroid dysfunction in high risk groups at a 17 tertiary referral center in eastern Nepal. The worldwide prevalence of hypothyroidism in various studies shows a remarkable variation and current prevalence ranges from 1% 18 to 20% for sub-clinical and 1-2% for overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Similar study observed 30% of the population suffering from thyroid dysfunction in high risk groups at a 17 tertiary referral center in eastern Nepal. The worldwide prevalence of hypothyroidism in various studies shows a remarkable variation and current prevalence ranges from 1% 18 to 20% for sub-clinical and 1-2% for overt hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of concentrations of A. millefolium extracts on contraction induced by KCl and acetylcholine were measured. After 30min incubation of the tissue with 1μM propranolol at concentration (Vanner et al, 1999) and 20min with 100 μM L-NAME at concentration (Hamm et al, 1999) the previous steps were repeated. To investigate the role of extracellular calcium in the extracts, the tissues in calcium-free Tyrode's solution containing KCL concentration (120mM) were placed and the cumulative CaCl2 (0.225-3.6 mM) was added to the bathroom.…”
Section: Methodsmentioning
confidence: 99%
“…Para este fim, exame de antígeno fecal é superior ao exame microscópico (25,26) . O exame de fezes para outros parasitas, em estudos realizados em grande escala nos EUA, não trouxe benefício (27) , mas isto pode não ser verdade em outros países onde parasitas são mais comuns. A perda de peso e a diarreia crônica devem levantar a possibilidade de infecção por HIV e o paciente deve ser questionado sobre o abuso de drogas injetáveis ou relações sexuais sem proteção com múltiplos parceiros.…”
Section: Anamneseunclassified